INDUSTRI ASURANSI JIWA DIGITAL DALAM PERSPEKTIF HUKUM POSITIF INDONESIA - Sherlly Febrianty; Helena Primadianti Sulistyaningrum (Fakultas Hukum Universitas Sriwijaya, 2024)
As the world develops, technology is increasingly developing. Many things can be used as new business opportunities for companies, including insurance companies. Article 1 number 1 of Law Number 40 of 2014 concerning Insurance reads,